The Higher Education Opportunity Act of 2008: What Does it Mean to Learners of Nontraditional Age Who Experience Intellectual Disability? - Kara Thrasher-Livingston (Adult Education Research Conference, 2009)
Analysis of discourse between the Higher Education Opportunity Act of 2008 and related public commentary reveals assumptions about learners who experience intellectual disability who potentially engage with postsecondary education. What does it mean for the nontraditional age adult learner?